PENERAPAN TEOREMA BINOMIAL UNTUK MENENTUKAN PELUANG KEJADIAN (KASUS :PERCOBAAN PELEMPARAN KOIN TAK SEIMBANG) - Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2016)
Study on trial coins and dice unbalanced still rare. This resulted in the students find it difficult when faced with the problem experiment coin toss and dice made in such a way that it becomes unbalanced. Actual trial coin toss and dice are balanced or unbalanced have the same pattern. For example in terms of determining the number of sample points, where the pattern is formulated as apn where p is the number of comparisons. Calculating the sample points and calculate the probability of the occurrence of an experiment throwing a coin or dice are balanced relatively easier than calculate the sample points and calculate the probability of occurrence of throwing a coin or dice experiment that is not balanced. Binomial Theorem extremely helpful in calculating pass up the opportunity of an event. However, due to the experimental throwing a coin or dice are balanced relatively easy then very rarely do calculations chance occurrence by using the Binomial Theorem.